Marine spatial planning (MSP): A first step to ecosystem-based management (EBM) in the Wider Caribbean - Ogden, John C (Revista de Biología Tropical, 2010)
The rapid decline of coastal ecosystems of the Wider Caribbean is entering its fifth decade. Some of the best science documenting this decline and its causes has been done by the laboratories of the Association of Marine Laboratories of the Caribbean (AMLC). Alarmed at the trends, Caribbean conservation pioneers established marine protected areas (MPAs) which spread throughout the region. Unfortunately, many have little or no protection and are now known to be too small to be effective in sustaining coastal ecosystems. Marine spatial planning (MSP) holds much promise to encompass the large geographic scales of the ecological processes and human impacts that influence coastal ecosystems and adjacent lands. The AMLC, through the scientific expertise and the national political connections of its member institutions, is well-positioned to help implement a pilot project. MSP a first step in ecosystem-based management and has had considerable success elsewhere. It holds our best chance of sustaining human use and conserving the coral reefs and associated ecosystems.